„Piosenkarz w sta...”, lub utajony stalinizm Michaiła Bułchakowa - Shteinbuk, Feliks (Przegląd Rusycystyczny, 2022)
FELIKS SHTEINBUK. «A SINGER IN A STA ...», OR LATENT STALINISM OF MIKHAIL BULGAKOV. The article analyses the implementation of one of the leading themes of Mikhail Bulgakov’s literary works, which concerns the confrontation between the artist and the authorities. In this regard, the aim of the research is defined as an attempt to discover and substantiate the real meaning of this theme, using biographical, cultural-historical and comparative-typological methods. As a result of the analysis of mainly the novel The Master and Margarita and the play Batum, the conclusion is made that the writer's artistic world is characterized by latent and conscious Stalinism, therefore the writer is trying to de-demonize and humanize the images of Woland and Stalin which correlate with each other.